Clinical impact of extensive molecular profiling in advanced cancer patients. Issue 1 (December 2017) - Cousin, Sophie; Grellety, Thomas; Toulmonde, Maud; Auzanneau, Céline; Khalifa, Emmanuel; Laizet, Yec'han; Tran, Kevin; Le Moulec, Sylvestre; Floquet, Anne; Garbay, Delphine; Robert, Jacques; Hostein, Isabelle; et al.
Abstract Previous precision medicine studies have investigated conventional molecular techniques and/or limited sets of gene alterations. The aim of this study was to describe the impact of the next-generation sequencing of the largest panel of genes used to date in tumour tissue and blood in the context of institutional molecular screening programmes. DNA analysis was performed by next-generation sequencing using a panel of 426 cancer-related genes and by comparative genomic hybridization from formalin-fixed and paraffin-embedded archived tumour samples when available or from fresh tumour samples. Five hundred sixty-eight patients were enrolled. The median number of prior lines of treatment was 2 (range 0–9). The most common primary tumour types were lung (16.9%), colorectal (14.4%), breast (10.6%), ovarian (10.2%) and sarcoma (10.2%). The median patient age was 63 years (range 19–88). A total of 292 patients (51.4%) presented with at least one actionable genetic alteration. The 20 genes most frequently altered wereTP53, CDKN2A, KRAS, PTEN, PI3KCA, RB1, APC, ERBB2, MYC, EGFR, CDKN2B, ARID1A, SMAD4, FGFR1, MDM2, BRAF, ATM, CCNE1, FGFR3 andFRS2 . One hundred fifty-nine patients (28%) were included in early phase trials. The treatment was matched with a tumour profile in 86 cases (15%). The two main reasons for non-inclusion were non-progressive disease (31.5%) and general status deterioration (25%). Twenty-eight percent of patients presented with a growth modulation index (time to progression under the early phase trial treatment/time to progression of the previous line of treatment) >1.3. Extensive molecular profiling using high-throughput techniques allows for the identification of actionable mutations in the majority of cases and is associated with substantial clinical benefit in up to one in four patients.